Comparison of Intra-CL Injection and Peripheral Application of Prostaglandin F2α Analog on Luteal Blood Flow and Secretory Function of the Bovine Corpus Luteum - Jonczyk, Agnieszka W.; Piotrowska-Tomala, Katarzyna K.; Skarzynski, Dariusz J. (Frontiers in Veterinary Science, 2022)
We investigated the effects of different doses of dinoprost injected directly into the bovine corpus luteum (CL) on (i) concentrations of progesterone (P4) and oxytocin (OT) in peripheral blood and (ii) mRNA levels of steroidogenesis- and necroptosis-related factors in CL tissue. Moreover, we examined the effects of dinoprost, injected intra-CL or administered intramuscularly (IM), on CL secretory function and on indicators of CL vascular network status: luteal tissue area (LTA), CL blood flow (CLBF), and the CLBF:LTA ratio (Adj. CLBF), in cows at the early and mid-luteal phases. In the Experiment 1, cows (day 10 of the cycle) were allocated to (i) an intra-CL injection of saline (control; n = 3); (ii) an intra-CL injection of dinoprost (1.25 mg; 2.5 mg, or 5 mg; n = 3 for each dose); (iii) an IM administration of saline (control; n = 3); or (iv) an IM administration of dinoprost (25 mg; positive control; n = 3). Concentrations of OT and P4 were measured in plasma samples. The mRNA expression of steroidogenesis- or necroptosis-related factors was determined in CL tissue 4 h after treatments. In Experiment 2, cows on day 4 (n = 12) or day 10 (n = 12) were allocated to (i) an intra-CL injection of dinoprost (2.5 mg/0.5 ml; n = 6), or (ii) IM administration of dinoprost (25 mg/5 ml; n = 6). Concentrations of P4 were measured in plasma samples. Luteal tissue area, CLBF, and Adj. CLBF were assessed based on colour Doppler ultrasonography. An intra-CL injection of dinoprost increased OT and decreased P4 levels in the jugular vein in a dose-dependent manner in cows at the mid-luteal phase. Increased CLBF and Adj. CLBF, accompanied by reduced P4 levels, were observed 2 h after intra-CL dinoprost injection in middle-stage CL. Decreased STAR and increased RIPK1 and RIPK3 mRNA levels confirmed that 2.5 mg dinoprost injected directly into CL is the minimum dose that induces luteolytic cascade. Injection of dinoprost directly into the CL (at a dosage lower than recommended for peripheral application) results in a pattern similar to IM dinoprost administration.